EFEKTIVITAS METODE PROJECT BASED LEARNING BERBASIS FILMORA DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Abdul Aziz Al Faruq; Agus Pahrudin; Imam Syafe'i (Jurnal Bilqolam Pendidikan Islam, 2024)
This study aims to assess the effectiveness of using Filmora in Project Based Learning (PjBL) to enhance student performance in Islamic Religious Education (PAI). The expectation is that integrating Filmora into the PjBL approach will boost student engagement and improve learning outcomes through the creation of engaging video content and project-based activities. Employing a quantitative experimental design, this study involved two student groups: an experimental group utilizing the Filmora-based PjBL method and a control group following traditional methods. Data collection included assessments of learning outcomes and observations of student activities. Analysis revealed that students in the Filmora-based PjBL group demonstrated a significant improvement in understanding PAI content compared to the control group. The results suggest that incorporating Filmora into the PjBL framework is an effective strategy for enhancing learning quality and outcomes in PAI. This research advocates for the integration of technology into teaching methods to enrich the learning experience and boost student skills.